Perbuatan Melawan Hukum Menghilangkan Hak Penggugat sebagai Pemenang Lelang dalam Putusan Pengadilan Perkara Nomor 379/PDT.G/2020/PN.JKT.PST (Neolectura, 2023)
Implementation of auctions, especially with practice, the potential for lawsuits is high. Claims with auction submissions as well as after auctions. The plaintiff's intention is to postpone its implementation. These lawsuits vary, with many cases of auction practice. Petitum himself with his tort, with what he did. The formulation of the problems discussed are: 1) What are the legal consequences for the defendant who commits an unlawful act eliminating the plaintiff's rights as the winner of the auction? ; and 2) What are the legal considerations of the judges in deciding the case for Court Decision Number 379 / PDT.G / 2020 / PN.JKT.PST?. The study method used is normative juridical. Based on the results of the study, the authors then outline the legal consequences for the defendant who committed it based on the provisions of Article 1365 by explaining if any unlawful act is required by those for whom they have a fault in compensation. Based on the four elements; a) It is against the law; b) Incurring a loss; c) Done with the wrong thing and d) His actions were detrimental which appeared causally. as in the consideration of the judge before dropping the decision Number 379/PDT.G/2020/PN.JKT.PST, that it is necessary for the Plaintiff to explain the credit facility from PT. Bank Negara Indonesia (Persero), Tbk. c.q. Sentra Kredit Kecil (SKC) Kramat in this lawsuit is intended to provide a clear picture to the Court of what matters are the Plaintiff's loss so that the nature of the maladministration action carried out by the Defendant a quo can qualify as an act contrary to law.